Knowledge Management of Village Funds of Channasut, Village 7, Phochongai Sub-district, Bang Rachan District, Sing Buri Province - Teedee, Thatchapon; Pansamai , Juthamard; Sanwised, Chalida (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
Knowledge management is perceived as an essential mechanism and tool to developman and organization in order to increase organization efficiency and prevent loss of knowledge by means of systematic cognitive management. The objectives of this research were to study 1) the knowledge management regarding the village funds of Channasut , Village 7, Phochongai Sub-district, Bang Rachan District, Sing Buri Province and 2) the administration model of the village funds of Channasut, Village 7, Phochongai Sub-district, Bang Rachan District, Sing Buri Province. This study employed the qualitative method, and the sample, selected by purposive sampling, was nine village fund committee members. The instruments comprised documentary research, interview, and group discussion. The data were analyzed through content analysis and verified by means of triangulation technique and thematic analysis as well. The results revealed that 1) the management knowledge of village funds consisted of five significant stages, namely 1. Knowledge Identification in regard to structure, fund, and management, 2. knowledge creation and acquisition such as trainings, seminars, formal and informal exchanges among committee members, 3. Knowledge management related to written records of a funding system, 4. knowledge codification with a simple and uncomplicated document system, and 5. Knowledge Transfer and utilization with continuous development; 2) the model of village fund administration included 1. identification of clear goals, 2. leadership, 3. personnel recruitment, 4. effective benefit distribution, 5. risk management, and 6. participation process.